The Impact of Technology and Change Management on Value Proposition Innovation - Hajishirzi, Reihaneh (2022)
Hajishirzi, R., Costa, C. J., & Aparicio, M. (2022). The Impact of Technology and Change Management on Value Proposition Innovation: An Iranian Study. Ieee Transactions On Engineering Management. https://doi.org/10.1109/TEM.2022.3225664 --- Funding: The authors acknowledge financial support via ADVANCECSG from the Fundação para a Ciência and Tecnologia (FCT Portugal) through research grant number UIDB/04521/2020, and we gratefully acknowledge the financial support from FCT—Fundação para a Ciencia e Tecnologia, I.P. (Portugal), and national funding through research grant UIDB/04152/2020—Centro de Investigação em Gestão de Informação (MagIC).